ANTICANCER DRUGS AS PROSPECTIVE EFFLUX PUMP INHIBITORS FOR SALMONELLA TYPHI PRODUCE CONFLICTING RESULTS IN IN SILICO AND IN VITRO STUDIES - Gupta, Pranjali; Gautam, Pankaj; Rai, Nishant (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Anticancer drugs paclitaxel and vinblastine were tested for their potential as efflux pump inhibitors for Salmonella Typhi-based on in silico and in vitro studies. Methods: Three-dimensional protein models of AcrAB-TolC of Salmonella Typhi were generated by online server PHYRE-2. The quality of 3D structures was assessed by PROCHECK, SWISS MODEL. Docking analysis of anticancer drugs with AcrA, AcrB and TolC subunits were performed after refining the homology models with Modrefiner. Salmonella Typhi (S. Typhi) efflux pump activity was measured by ethidium bromide (EtBr) cartwheel and semi-automated fluorometry methods respectively. Fluorescence intensity in bacterial colonies was measured under different treatment conditions (with or without drugs) on Muller Hinton agar (MHA) plates containing EtBr in cartwheel assay. EtBr efflux assay was determined following the loading of bacteria with EtBr and fluorescence was recorded over fixed time period with the help of fluorescent spectrophotometer. The results obtained were compared with the control. Results: Efflux pump inhibitor (EPIs) activity of paclitaxel and vinblastine determined by EtBr cartwheel assay registered no activity whereas semi-automated fluorescent assay revealed marginal activity when compared to control. Conclusion: We report the conflicting result of in silico and in vitro studies in predicting the antimicrobial effect of mainstream anticancer drugs as efflux pump inhibitors for Salmonella Typhi.